ANTI-OBESITY POTENTIAL OF CYPERUS ROTUNDUS L. AQUEOUS TUBER EXTRACT IN RATS FED ON HIGH FAT CAFETERIA DIET - K, Athesh; M, Divakar; P, Brindha (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: This study was undertaken to evaluate the anti-obesity potential of the aqueous tuber extract of Cyperus rotundus L. (ATECR) in high fat cafeteria diet (HFCD) fed obese rats. Methods: Wistar strain of albino rats were divided into six groups comprising of six rats each. Group I served as normal control fed with normal pellet chow, group II served as disease control fed with high fat cafeteria diet, group III, IV and V animals, received ATECR at a dose level of 100, 200 and 300mg/kg bw along with HFCD for 40 days, while, group VI served as standard drug control, which received Orlistat at a dosage of 50mg/kg bw along with HFCD. Results: Administration of HFCD for 40 successive days to experimental rats significantly increased the body weight, organ and fat pad weights, serum total cholesterol, LDL cholesterol, VLDL cholesterol, triglycerides and glucose levels; and decreased HDL cholesterol as compared to normal control. While treatment with ATECR showed a significant reduction in the body weight gain, organ weight of the liver, kidney, spleen, weight of fat pads and the levels of serum triglycerides, total cholesterol, LDL cholesterol, VLDL cholesterol, glucose and increase in HDL cholesterol in a dose dependent manner. Further, the levels of liver markers such as aspartate transaminase (AST), alanine transaminase (ALT) and alkaline phosphatase (ALP), which were found to be elevated in the serum of obese rats, also resumed to normal on treatment with different concentrations of ATECR. Moreover, the consumption of ATECR reduced oxidative stress by enhancing the levels of glutathione (GSH), glutathione peroxidase (GPx), super oxide dismutase (SOD) and catalase in the hepatic tissue of rats with HFCD induced obesity. Conclusion: These results demonstrate clearly that repeated oral administration of tubers of Cyperus rotundus L. aqueous extract can evoke a potent anti-obesity activity. Â Keywords: High Fat Cafeteria diet, Obesity, Cyperus rotundus L., Orlistat.